Exposure of low-temperature plasma after vaccination in tongue promotes systemic IgM induction against spike protein of SARS-CoV-2. (2nd January 2023) - Sato, Kotaro; Fujii, Kouki; Tanaka, Hiromasa; Hori, Masaru; Hibi, Hideharu; Toyokuni, Shinya
Abstract: COVID-19 has been pandemic since 2020 with persistent generation of new variants. Cellular receptor for SARS-CoV-2 is angiotensin-converting enzyme 2 (ACE2), where transmembrane serine protease-2 (TMPRSS2) is essential for viral internalization. We recently reported abundant expression of ACE2 and TMPRSS2 in the oral cavity of humans and mice. Therefore, oral cavity may work for COVID-19 infection gates. Here we undertook to evaluate whether vaccination in the tongue harbors any merit in comparison to subcutaneous injection. Low-temperature plasma (LTP) is the fourth physical state of matters with ionization above gas but at body temperature. LTP provides complex chemistry, eventually supplying oxidative and/or nitrosative stress on the interface. LTP-associated cellular death has been reported to cause apoptosis and/or ferroptosis. However, there is few data available on immunogenicity retention after LTP exposure. We therefore studied the effect of LTP exposure after the injection of keyhole limpet hemocyanin (KLH) or spike 2 protein of SARS-CoV-2 to the tongue of six-week-old male BALB/c mice, compared to subcutaneous vaccination. Whereas LTP did not change the expression of ACE2 and TMPRSS2 in the tongue, repeated LTP exposure after tongue vaccination significantly promoted systemic and specific IgM production at day 11. In contrast, repeated LTP exposure after subcutaneous vaccination of KLH decreased systemic IgM production. Of note, tongue injection produced significantly higher titer of IgM and IgG in the case of KLH. In conclusion, LTP significantly reinforced humoral immunity by IgM after tongue injection. Vaccination to the tongue can be a novel strategy to acquire immediate immunity.